Sodium sulphide facility at Bridesburg plant - Rohm and Haas Company (Exterior views of Charles Lennig and Company plant in Bridesburg, 1931)
Exterior view of a section of the sodium sulfide manufacturing facility (Building 26) at the Charles Lennig and Company chemical manufacturing plant in Bridesburg, a neighborhood located along the Delaware River in the Northeast section of Philadelphia, Pennsylvania. Charles Lennig and Company operated as a subsidiary of the Rohm and Haas Company, an international chemical company headquartered in Philadelphia, from 1920 to 1947.
Keywords: Chemical industry; Charles Lennig and Company, Inc.; Pennsylvania--Philadelphia--Bridesburg; Rohm and Haas Company; Corporations